Bioelectrochemical element conversion reactions towards generation of energy and value-added chemicals. (March 2020) - Sun, Min; Zhai, Lin-Feng; Mu, Yang; Yu, Han-Qing
Abstract: In the past decades, the bioelectrochemical system (BES) has developed into a versatile platform to sustain the conversion of various substances for the generation of energy and energy-efficient production of chemicals. Taking advantage of microbial extracellular electron transfer, the BES is able to perform a variety of value-added element conversion reactions, including production of electric energy from organic carbon, synthesis of chemicals from carbon dioxide, oxidation of sulfide into element sulfur, reduction of nitrate/nitrite into nitrous oxide and reduction of metal ions into solid metals and/or metal oxides. While the potential for using BES as an energy and resource factory has been fully recognized, governing the element conversion pathways into the desired energy and products in BES is still a great challenge. This review provides comprehensive insights into the microbial extracellular electron transfer principles as well as behaviors of key chemical elements in BESs. Individual element conversion processes and their integrations on the BES platform are analyzed. The physicochemical, chemical and microbial mechanisms involved in these processes are explored, and the coupling patterns of electron transfer and element conversion reactions are elucidated. Furthermore, the challenges to design, construct and operate a BES with improved electron transfer efficiency and product specificity are discussed, and research needs are proposed. Additionally, BES technologies from the perspectives of waste remediation, energy production, resource recovery and chemical synthesis are envisaged.